2020
DOI: 10.1101/2020.06.05.135228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AIM2 Inflammasome Mediates Hallmark Neuropathological Alterations and Cognitive Impairment in a Mouse Model of Vascular Dementia

Abstract: Chronic cerebral hypoperfusion is associated with vascular dementia (VaD). Cerebral hypoperfusion may initiate complex molecular and cellular inflammatory pathways that contribute to long term cognitive impairment and memory loss. Here we used a bilateral common carotid artery stenosis (BCAS) mouse model of VaD to investigate its effect on the innate immune response – particularly the inflammasome signaling pathway. Comprehensive analyses revealed that chronic cerebral hypoperfusion induces a complex temporal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 63 publications
5
21
0
Order By: Relevance
“…Increased expression and release of the inflammatory cytokine IL-6 are observed in HF patients (54). IL-6 promotes the infiltration and activation of mononuclear leukocytes (55) and activates the coagulation pathway and vascular endothelial cells, but inhibits myocardial function (56). In the present study, we found that M1 macrophage infiltration into the heart and the expression of IL-6 in the heart were elevated after BCAS, which may contribute to BCAS-induced cardiac dysfunction.…”
Section: Bcas Increases Cardiac Inflammationsupporting
confidence: 53%
“…Increased expression and release of the inflammatory cytokine IL-6 are observed in HF patients (54). IL-6 promotes the infiltration and activation of mononuclear leukocytes (55) and activates the coagulation pathway and vascular endothelial cells, but inhibits myocardial function (56). In the present study, we found that M1 macrophage infiltration into the heart and the expression of IL-6 in the heart were elevated after BCAS, which may contribute to BCAS-induced cardiac dysfunction.…”
Section: Bcas Increases Cardiac Inflammationsupporting
confidence: 53%
“…We recently demonstrated that 30 days of cerebral hypoperfusion due to BCAS results in hippocampal neuronal loss (45). In the present study it is noteworthy that,…”
Section: Discussionsupporting
confidence: 50%
“…We recently demonstrated that 30 days of cerebral hypoperfusion due to BCAS results in hippocampal neuronal loss (45). In the present study it is noteworthy that, compared with young sham mice, basal CBF was similarly reduced in old sham mice and in young mice subjected to cerebral hypoperfusion for 7 or 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AIM2 regulates the viability and apoptosis of human colorectal cancer cells via the PI3K/AKT signaling pathway (31). It has been demonstrated that, in AIM2 knockout mice, the production of pro-inflammatory cytokines mediated by the inflammasome is reduced, and apoptosis and pyroptosis are attenuated (32). Furthermore, AIM2 inhibits the invasion and metastasis of kidney cancer cells by enhancing autophagy induction (33).…”
Section: Discussionmentioning
confidence: 99%